The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1063/1.471520
|View full text |Cite|
|
Sign up to set email alerts
|

The structure of alkali halide dimers: A critical test of ionic models and new abinitio results

Abstract: The structure of alkali halide dimers: A critical test of ionic models and new ab initio results. T. Torring, S. Biermann, J. Hoeft, R. Mawhorter, R. J. Cave, and C. Szemenyei, J. Chem. Phys. 104, 8032 (1996) In semiempirical ionic models a number of adjustable parameters have to be fitted to experimental data of either monomer molecules or crystals. This leads to strong correlations between these constants and prevents a unique test and a clear physical interpretation of the fit parameters. Moreover, it is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…For clusters, a decisive point is also what kind of crystal structure they adopt in the process of self-assembling from the gas-phase monomers to (molecules). In several earlier works it has been suggested that alkali metal halide clusters were cuboids (rectangular parallelepipeds with an even number of atoms along at least one of the edges). ,, During the later time it has been theoretically shown that for the ionic clusters with the number of atoms below 100 the ratio of the cation and anion radii, r C / r A , defined whether a tubular or cubic geometry would be energetically favorable. ,, If r C / r A ≤ 0.5, tubular structures occur to be more stable. Potassium chloride belongs to those alkali metal halides for which this criterion allows assuming cubic geometry for all cluster sizes because r C ≈ r A in this case.…”
Section: Ionic Model and The Role Of Its Main Parameters For Alkali M...mentioning
confidence: 99%
See 2 more Smart Citations
“…For clusters, a decisive point is also what kind of crystal structure they adopt in the process of self-assembling from the gas-phase monomers to (molecules). In several earlier works it has been suggested that alkali metal halide clusters were cuboids (rectangular parallelepipeds with an even number of atoms along at least one of the edges). ,, During the later time it has been theoretically shown that for the ionic clusters with the number of atoms below 100 the ratio of the cation and anion radii, r C / r A , defined whether a tubular or cubic geometry would be energetically favorable. ,, If r C / r A ≤ 0.5, tubular structures occur to be more stable. Potassium chloride belongs to those alkali metal halides for which this criterion allows assuming cubic geometry for all cluster sizes because r C ≈ r A in this case.…”
Section: Ionic Model and The Role Of Its Main Parameters For Alkali M...mentioning
confidence: 99%
“…The corresponding calculations show that though in a class of cases the cluster properties are close to those of the solid, for some types of clusters with ionic bonding the electronic and geometric structure may deviate significantly from those adopted at macroscale. For example, for the alkali metal halide clusters containing up to10 2 atoms the possibility of a structure with tubular geometry minimizing the energy to a degree higher than the solid-like cubic geometry continues to be a subject of theoretical investigation since Aguado et al suggested it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Matrix isolation studies of the vibrational frequencies of Cs 2 Br 2 and Cs 2 I 2 have also been recently published. 28 The literature is peppered with many theoretical studies 16,[29][30][31][32][33] which have some difficulty in reproducing the highly accurate microwave monomer distances.…”
Section: Introductionmentioning
confidence: 99%
“…Molecule-Dependent Constants for Determining the Saturation Pressures (A i and B i ) of Alkali Bromides, Effective Molecular Diameters in the N 2 Atmosphere (d i,eff ), Effective Mass in the N 2 Atmosphere (μ i ), and Density at Room Temperature (ρ i )30,41,42 …”
mentioning
confidence: 99%